2018
DOI: 10.3892/mmr.2018.8781
|View full text |Cite
|
Sign up to set email alerts
|

ATM‑JAK‑PD‑L1 signaling pathway inhibition decreases EMT and metastasis of androgen‑independent prostate cancer

Abstract: Castration-resistant prostate cancer (CRPC), also known as androgen-independent prostate cancer, frequently develops local and distant metastases, the underlying mechanisms of which remain undetermined. In the present study, surgical specimens obtained from patients with clinical prostate cancer were investigated, and it was revealed that the expression levels of ataxia telangiectasia mutated kinase (ATM) were significantly enhanced in prostate cancer tissues isolated from patients with CRPC compared with from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 46 publications
0
26
0
Order By: Relevance
“…They discovered that polyphyllin I, a natural compound, can reverse EMT by regulating the IL-6/STAT3 signaling pathway in non–small cell lung cancer [25]. Moreover, Zhang et al have determined that EMT can be regulated in prostate cancer by the ataxia telangiectasia-mutated ( ATM ) protein kinase/STAT3/PD-L1 signaling pathway and that PD-L1 is significantly reduced when ATM is knocked down [26]. Asgarova et al also observed upregulated PD-L1 during EMT and described tumor cells' increased proliferation, infiltration, and migration capacities and greater ability to escape immune system detection during EMT [27].…”
Section: Discussionmentioning
confidence: 99%
“…They discovered that polyphyllin I, a natural compound, can reverse EMT by regulating the IL-6/STAT3 signaling pathway in non–small cell lung cancer [25]. Moreover, Zhang et al have determined that EMT can be regulated in prostate cancer by the ataxia telangiectasia-mutated ( ATM ) protein kinase/STAT3/PD-L1 signaling pathway and that PD-L1 is significantly reduced when ATM is knocked down [26]. Asgarova et al also observed upregulated PD-L1 during EMT and described tumor cells' increased proliferation, infiltration, and migration capacities and greater ability to escape immune system detection during EMT [27].…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that the ATM inhibitor KU-55933 can hinder cancer cell proliferation by inducing G1 blockade and thereby triggering apoptosis in cancer cells [39]. Liu R et al also revealed that ATM deletion could dramatically decrease the proliferation, migration and invasion of colon cancer cells [40], which could also lead to a remarkable reduction in migration and epithelial-mesenchymal transition (EMT) in prostate cancer cells [41]. In our experiment, ATM was confirmed to be the downstream target gene of miR-203a-3p through bioinformatics prediction and a dual-luciferase reporter gene assay.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, PD‐L1 has been verified to be associated with JAK activation . Intriguingly, ATM‐JAK‐PD‐L1 signaling pathway has been discovered to promote EMT and metastasis of androgen‐independent prostate cancer . In present study, we firstly uncover that SNHG20 modulates the levels of p‐ATM, p‐JAK1/2, and PD‐L1 in ESCC cells.…”
Section: Discussionmentioning
confidence: 65%